Apuleius as ‘extrarius’ in the city of Oea: family and cultural conflicts in Africa Proconsularis - Lima Neto, Belchior Monteiro (Romanitas - Revista de Estudos Grecolatinos, 2017)
The identification of Apuleius as magus generally leads us to understand the facts that occurred to him in Oea only by his association with magic, which, in our opinion, would greatly restrict our interpretations. A considerable part of the opposition of the elite of Oea against Apuleius extrapolated exoteric and miraculous questions, relating more specifically to the fact that the author was considered a homo extrarius, an outsider who had broken the social place destined for him in the city. The understanding of such events comes to some extent from the analysis of Apuleius’s meddling in matters pertaining to family and political inheritances, endowments and alliances, which aid us to understand the very animosity of Apuleius in the urban environment of Oea.